Development of a Problem-Solving-Based Mathematics E-Module to Enhance Students' Critical Thinking Skills - Ahmad Fauzani; Nuraisyah Rahma; Mario Jessy Luzon (LOGIKA: Jurnal Pendidikan Matematika, 2026)
Critical thinking skills are essential competencies in twenty-first-century mathematics education. However, numerous studies indicate that students' mathematical critical thinking abilities remain relatively low due to the limited availability of instructional materials that facilitate systematic problem-solving activities. This study aimed to develop a problem-solving-based mathematics e-module that is valid, practical, and effective in improving students' critical thinking skills. The research employed a Research and Development (R&D) method using the ADDIE model consisting of analysis, design, development, implementation, and evaluation stages. The participants were 72 eighth-grade junior high school students. Research instruments included expert validation sheets, student response questionnaires, and critical thinking tests. Data were analyzed using descriptive statistics and N-Gain tests. The findings revealed that the developed e-module achieved a validity level of 92.4%, practicality of 89.7%, and effectiveness with an N-Gain score of 0.74 categorized as high. Students’ average critical thinking score increased from 61.32 in the pretest to 84.78 in the posttest. These findings indicate that problem-solving-based mathematics e-modules effectively enhance students’ critical thinking skills. This study contributes to the development of digital instructional materials supporting twenty-first-century learning and the implementation of the Independent Curriculum.